2022
DOI: 10.1177/21582440221079908
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Induced Teleworking Arrangements on Employees in NGOs: Implications for Policy and Practice for Leadership

Abstract: The article sought to address real or perceived “teleworking hesitancy” by generating empirical evidence on employee exposure to teleworking in a global south context. The results of the empirical investigation were integrated with the growing body of research on the future of the post-pandemic workplace. The results depicted the opposite and significant effects of perceived workload and organizational teleworking support on employee teleworking experience and the (growing) desire to utilize flexible working o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The findings further indicated that employees faced some challenges because of fundamental issues such as not having appropriate working conditions, increased workload, and limited interaction with team members. Sanhokwe et al (2022) confirmed an increased work load brought upon telework. Employees often cross the boundaries between non-work and work activities, making it challenging to work from home (Fisher et al, 2020; Ramarajan & Reid, 2013).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The findings further indicated that employees faced some challenges because of fundamental issues such as not having appropriate working conditions, increased workload, and limited interaction with team members. Sanhokwe et al (2022) confirmed an increased work load brought upon telework. Employees often cross the boundaries between non-work and work activities, making it challenging to work from home (Fisher et al, 2020; Ramarajan & Reid, 2013).…”
Section: Discussionmentioning
confidence: 66%
“…Working from home was previously an option of preference for employees; however, with the rise in COVID-19 cases, it became mandatory for employees to complete their professional tasks at home (Kniffin et al, 2021;Venkatesh, 2020. The findings further indicated that employees faced some challenges because of fundamental issues such as not having appropriate working conditions, increased workload, and limited interaction with team members. Sanhokwe et al (2022) confirmed an increased work load brought upon telework. Employees often cross the boundaries between non-work and work activities, making it challenging to work from home (Fisher et al, 2020;Ramarajan & Reid, 2013).…”
Section: Discussionmentioning
confidence: 66%
“…Results from a qualitative study by Sanhokwe et al (2022, in review) in the same study context suggest that certain unique elements underpin the decent work phenomenon beyond the dictates of current theory and conceptualisations. Further studies in similar contexts will add value to the current debates on the phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…A convenient sample, drawn using the snowball technique, was derived from employees serving in nongovernmental organisations (NGOs) in Zimbabwe and Eswatini. Although most nonessential service providers were instructed to halt their operations as part of the efforts to mitigate the spread of the coronavirus disease 2019 (COVID-19) services, NGOs continued to provide (Sanhokwe et al, 2022;Wilke et al, 2020). Hence, the choice to situate the study in the NGO sector.…”
Section: Methodsmentioning
confidence: 99%
“…Working from home implies that employees consciously or subconsciously transition across the work and nonwork domains in a seamless manner (Sanhokwe et al, 2022).…”
Section: Model and Hypothesesmentioning
confidence: 99%